What is a real measure of corporate liquidity - Melik Ertugrul; Ali Coskun (International Journal of Management and Economics, 2021)
The financial health hypothesis argues that the valuation multiple of book value of equity (earnings) increases (decreases) as financial health decreases. By considering the liquidity dimension of financial health, we analyze an accrual-based liquidity ratio (current ratio) and a cash-based liquidity ratio (OCF ratio) from the perspective of this hypothesis. Using the median values of these ratios, we divide the sample consisting of listed firms on Borsa Istanbul during 2009-2018 into two and document the ensuing outcomes. Valuation multiples of book value of equity and earnings are reported as being statistically indifferent between low-liquid and high-liquid subgroups obtained for the median current ratio. However, the valuation multiple of book value of equity (earnings) significantly increases (decreases) for the low-liquid subgroup below the median OCF ratio. As the latter is consistent with the financial health hypothesis, this study reveals that the OCF ratio is a more convenient and reliable measure of liquidity than the current ratio.
Keywords: G14; M21; M41; 650; cash flow statement; current ratio; financial health; liquidity; operating cash flows